TiO2-SiO2 nanofluid characterization: Towards efficient with water/ethylene glycol mixture for solar application - Mohd Amiruddin, Fikri; F. F., Asri; W. M., Faizal; Hasyiya Karimah, Adli; R., Mamat; W. H., Azmi; Najafi, Gholamhassan; Yusaf, Talal (IOP Publishing, 2020)
Nowadays renewable energy has been used widely as strong contenders to improve the plight of two billion people, mostly in rural areas, without access to modern forms of energy. In this study, the effect of using water/ethylene glycol-based TiO2-SiO2 nanofluid on the characteristic of the solar radiation test rig has been experimentally used to investigate the characteristic of TiO2-SiO2 nanofluid suspended in water/ethylene glycol for solar applications. The TiO2-SiO2 nanofluids were prepared at a volume concentration of 0.3, 0.5 and 0.7% and dispersed in a base fluid of water/ethylene glycol 60:40 and 70:30 TiO2-SiO2 with the one-step method. KD2 Pro measures thermal conductivity set equipment and viscosity by LVDV III Ultra Rheometer. Thermal conductivity results show that the increase with different temperatures but the temperature of viscosity decreases. For solar radiation test rig that the highest point indicates the end of the charging process and the beginning of the discharging process, the maximum concentrations of 0.7% are observed to consistently provide higher temperature output as compared to the other three concentrations of nanofluids based on solar radiation 300, 500 and 700 W/m2 . Therefore, it can be concluded that the higher concentrations give ample time to the test tube to transfer the heat and thus increased its temperature during the charging process.